The Influence of Environmental Factors, Perception, and Participation on Industrial Heritage Tourism Satisfaction—A Study Based on Multiple Heritages in Shanghai - Zhiguo Fang; Jiachen Yao; Jianing Shi (Buildings)
With the increasing public awareness and strength of industrial heritage protection, industrial heritage plays an increasingly important role in tourism after transformation and upgrading. The influence of built environment factors and visitors’ participation on satisfaction has been fully confirmed, but the primary and secondary relationships between the two variables remain unclear. The purpose of this study is to explore the relationships between the built environment, tourist participation, and tourism satisfaction, and compare the actual loads of different routes to find the dominant variable. The data of this study came from three industrial heritage renovation projects in Shanghai with remarkable transformation results. Field investigations and questionnaire surveys were conducted on them, and a total of 362 valid samples were received. Descriptive statistical analysis and structural equation models were used to analyze the data. Two paths of “built environment–tourism satisfaction” and “tourist participation–tourism satisfaction” are compared and demonstrated. The path coefficient of the former is 0.63, while that of the latter is 0.77, and the influence of the latter is more significant than that of the former. The study creatively found the audience orientation of both sexes for different types of experience activities, confirmed the mediating effect of subjective perception, and provided the following suggestions for managers of built industrial cultural heritage. Interactive experiences and guided tours deepen visitors’ understanding of the historical and cultural value of industrial heritage. Virtual reality and augmented reality technologies can be introduced to provide an immersive visit experience and attract a wider audience to participate, effectively enhancing the attractiveness of and satisfaction with industrial heritage tourism.